Food Analysis - Nielsen, S. Suzanne (Springer International Publishing : Imprint: Springer, 2017)
This fifth edition provides information on techniques needed to analyze foods for chemical and physical properties. The book is ideal for undergraduate courses in food analysis and is also an invaluable reference to professionals in the food industry. General information chapters on regulations, labeling, sampling, and data handling provide background information for chapters on specific methods to determine chemical composition and characteristics, physical properties, and objectionable matter and constituents. Methods of analysis covered include information on the basic principles, advantages, limitations, and applications. Sections on spectroscopy and chromatography along with chapters on techniques such as immunoassays, thermal analysis, and microscopy from the perspective of their use in food analysis have been expanded. Instructors who adopt the textbook can contact the editor for access to a website with related teaching materials.- Resumé vydavatel
Keywords: analýza potravin; potravinářská chemie; food analysis; food chemistry; elektronické knihy; kolektivní monografie; electronic books; collective monographs